Pengaruh Persentase Naungan Terhadap Pertumbuhan dan Hasil Tanaman Sawi Pagoda (Brassica narinosa L.) - Melani, Novika; Rahmawati, Rahmawati; Sumbari, Chika (CULTIVATE: Journal of Agriculture Science, 2025)
This study used a Randomized Block Design (RBD) with 4 treatments and 5 replications. The observational data were averaged and statistically analyzed using an F-test at a 5% significance level, followed by a DMRT test at the 5% significance level. The treatments were different shading percentages as follows: no shading, 55% shading, 65% shading, and 75% shading. The observed variables in this study included plant height (cm), number of leaves (pieces), maximum leaf width (cm), maximum leaf length (cm), crop diameter (cm), root length (cm), fresh weight per plant (grams), fresh weight per plot (grams), and fresh weight per hectare (tons). The results of the experiment showed that 55% shading increased maximum leaf length, maximum leaf width, crop diameter, and root length, while no shading increased the number of leaves and yield per plant of pagoda mustard.